2018
DOI: 10.1186/s12936-018-2289-2
|View full text |Cite
|
Sign up to set email alerts
|

Severe Plasmodium ovale malaria complicated by acute respiratory distress syndrome in a young Caucasian man

Abstract: BackgroundAlthough Plasmodium ovale is considered the cause of only mild malaria, a case of severe malaria due to P. ovale with acute respiratory distress syndrome is reported.Case presentationA 37-year old Caucasian man returning home from Angola was admitted for ovale malaria to the National Institute for Infectious Diseases Lazzaro Spallanzani in Rome, Italy. Two days after initiation of oral chloroquine treatment, an acute respiratory distress syndrome was diagnosed through chest X-ray and chest CT scan wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…However, P. ovale can cause severe complications and death [19,20]. Previous studies have reported that the severe complications of P. ovale infections include acute respiratory distress syndrome (ARDS) [21][22][23][24][25][26], renal impairment [24,27], jaundice, and hypotension [26,27]. The most recent study on severe P. ovale malaria in travelers and migrants demonstrated that 5.3% of patients with P. ovale developed severe complications according to the 2015 WHO criteria, including hyperbilirubinemia, pulmonary edema, shock, significant bleeding, and impaired consciousness [28].…”
Section: Introductionmentioning
confidence: 99%
“…However, P. ovale can cause severe complications and death [19,20]. Previous studies have reported that the severe complications of P. ovale infections include acute respiratory distress syndrome (ARDS) [21][22][23][24][25][26], renal impairment [24,27], jaundice, and hypotension [26,27]. The most recent study on severe P. ovale malaria in travelers and migrants demonstrated that 5.3% of patients with P. ovale developed severe complications according to the 2015 WHO criteria, including hyperbilirubinemia, pulmonary edema, shock, significant bleeding, and impaired consciousness [28].…”
Section: Introductionmentioning
confidence: 99%
“…P. ovale infection would not have been identified without a sensitive molecular test. P. ovale, which is now separated into the two sympatric species Plasmodium ovale curtisi and Plasmodium ovale wallikeri, is generally linked to rather mild disease but severe complications can develop [19]. The delay in the manifestation of symptomatic disease is characteristic even when atovaquone/proguanil chemoprophylaxis has been used.…”
Section: Discussionmentioning
confidence: 99%
“…Bronchitis COVID-19 X*** (11) X* (10) X** (13) X* (10) X*** (11) Dengue X* (12,17) X** (12) X** (12,17) X*** (12) X*** (12) Malaria X** (8 ) X** (1 ) X** (13 ) X** (1 ) X** (8 ) Streptococcus pneumoniae X** (9) X** (9) X*** (6) X** (6,9) X* (6,9) Tuberculosis X* (15,18) X** (2) X** (14) X* (15,2,18) X* (15,18) * ordinary; ** 40-60% of cases; *** uncommon; mon * are significantly different; ** are not significantly different.…”
Section: Rounded Morphological Opacitiesmentioning
confidence: 99%